Effects of weathering on the performance of self-cleaning photocatalytic paints. (February 2019) - Enea, D.; Bellardita, M.; Scalisi, P.; Alaimo, G.; Palmisano, L.
Abstract: The use of photocatalytic products for the surface coating of buildings is spreading more and more, because of the reduction of atmospheric pollutants and the colour maintenance of the paints over time with reduction of the maintenance costs and the improvement of the aesthetic appearance. The study reports the evaluation of the effects of the atmospheric conditions on three commercial photocatalytic paints containing TiO2 . In particular tests were carried out by using samples subjected to accelerated aging inside a climate chamber and naturally aged by exposure for two years to the external environment of the city of Palermo (representative of a coastal environment of the Mediterranean basin). The samples were characterized by Scanning Electron Microscopy (SEM) and Optical Microscopy to evaluate the surface morphology, and by UV–Vis Spectrophotometry to appreciate the colours changes as a result of aging. X-ray diffraction (XRD), moreover, was used to identify the TiO2 phase and static contact angles were determined to evaluate the surface hydrophilicity. The photocatalytic activity was evaluated under UV and solar light irradiation by degrading 2-propanol, used as a probe molecule and analysed by gas chromatography (GC), which is representative of volatile organic compounds (VOC's). The results indicated colour conservation, increase of the surface hydrophilicity and maintenance of the photocatalytic performances.